Characterization of Trehalose-6-phosphate Synthase and Trehalose-6-phosphate Phosphatase Genes and Analysis of its Differential Expression in Maize (Zea mays) Seedlings under Drought Stress - Acosta Pérez, Phamela; Camacho Zamora, Bianka Dianey; Espinoza Sánchez, Edward Alexander; Gutiérrez Soto, Juanita Guadalupe; Zavala García, Francisco; Abraham Juárez, María Jazmín; Sinagawa García, Sugey Ramona (Molecular Diversity Preservation International, 2020)
Maize is the most important crop around the world and it is highly sensitive to abiotic stress caused by drought, excessive salinity, and extreme temperature. In plants, trehalose has been widely studied for its role in plant adaptation to different abiotic stresses such as drought, high and low temperature, and osmotic stress. Thus, the aim of this work was to clone and characterize at molecular level the trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP) genes from maize and to evaluate its differential expression in maize seedlings under drought stress. To carry out this, resistant and susceptible maize lines were subjected to drought stress during 72 h. Two full-length cDNAs of TPS and one of TPP were cloned and sequenced. Then, TPS and TPP amino acid sequences were aligned with their homologs from different species, showing highly conserved domains and the same catalytic sites. Relative expression of both genes was evaluated by RT-qPCR at different time points. The expression pattern showed significant induction after 0.5 h in resistant lines and after two to four hours in susceptible plants, showing their participation in drought stress response.